Entrepreneurship-based School Management - Susan Febriantina; RR Ponco Dewi Karyaningsih; Munawaroh (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2020)
Community service activities were held on Saturday, July 27, 2019, at the Al Musthofaiyah Islamic Education Foundation, Beji Village, Depok City. This activity aims to provide assistance and training related to the concept of entrepreneurship-based school management and improve teacher competencies as entrepreneurs in the field of education at the Al Musthofaiyah educational foundation in Depok. The method of activities used in this activity is the integrated approach method, which integrates various learning techniques such as lectures, briefings, questions and answers, case studies, discussions, games, sharing experiences. The result achieved is that the trainees can understand and apply entrepreneurial-based school management systems